Histone deacetylase 6 inhibition improves survival in a swine model of lethal hemorrhage, polytrauma, and bacteremia. Issue 5 (November 2020) - Biesterveld, Ben E.; Wakam, Glenn K.; Kemp, Michael T.; Williams, Aaron M.; Shamshad, Alizeh; O'Connell, Rachel L.; Siddiqui, Ali Z.; Chtraklin, Kiril; Bhatti, Umar F.; Li, Yongqing; Alam, Hasan B.
Abstract : BACKGROUND: Trauma is the leading cause of death for young Americans. Nonspecific histone deacetylase inhibitors, such as valproic acid, have been shown to improve survival in preclinical models of lethal trauma, hemorrhage, and sepsis. The doses needed to achieve a survival benefit are higher than Food and Drug Administration–approved doses, and the nonspecificity raises concerns about unintended adverse effects. The isoform-specific histone deacetylase 6 inhibitor, ACY-1083, has been found to be as efficacious as valproic acid in a rodent model of hemorrhagic shock. We hypothesized that ACY-1083 treatment would improve survival in a swine model of lethal hemorrhage, polytrauma, and bacteremia. METHODS: Swine were subjected to 45% blood volume hemorrhage, brain injury, femur fracture, rectus crush, splenic and liver lacerations, and colon injury. After 1 hour of shock (mean arterial pressure, 30–35 mm Hg), animals were randomized to normal saline resuscitation (control) or normal saline plus ACY-1083 30 mg/kg treatment (n = 5/group). After 3 hours (simulating delayed evacuation), packed red blood cells and antibiotics were administered, the colon injury was repaired, and the abdomen was closed. Animals were then monitored for another 4 hours. Survival was assessed using Kaplan-Meier and log-rank test. RESULTS: This combination of injuries was lethal. All animals became bacteremic, in addition to the severe hemorrhagic shock. Survival in the control group was 0%, and ACY-1083 treatment increased survival to 80% ( p = 0.019). There was no difference in the brain lesion size between the groups. CONCLUSION: A single dose of ACY-1083 markedly improves survival in an otherwise lethal model of polytrauma, hemorrhagic shock, and bacteremia. Abstract : Supplemental digital content is available in the text.